Synthesis and evaluation of transparent polyurethane from liquefied bamboo residue as bio coating for wood surface coating - Mohammad Suffian James, Redzuan (2024)
Laminated bamboo products have emerged as a highly favoured means of utilising bamboo. These products necessitate multiple stages of processing, resulting in significant quantities of waste. A potentially viable strategy for maximising the utilisation of this biomass resource involves its conversion into polyurethane through the process of liquefaction. Despite numerous reported instances of successful attempts, the colour of bio-polyurethane derived from biomass exhibits significant variation, ranging from dark brown to nearly black. This variability poses a limitation on its application within the coating industry, where the attainment of high surface aesthetics is of paramount significance. The present study utilised residues derived from a bamboo processing mill as a precursor for the production of polyols, subsequently employed in the synthesis of bio-polyurethane. The residues consisted of a combination of four distinct species of bamboo, namely semantan (Gigantochloa scortechinii), beting (G. levis), betong (Dendrocalamus asper), and minyak (Bambusa vulgaris). The PEG 400 and glycerol liquefaction mixtures were combined in a ratio of 9:1. Optimal reaction conditions, including temperature and duration, were established by assessing the minimal percentage of residual bamboo after liquefaction. The results indicate that only temperature significantly affects the percentage of residual bamboo. At 150°C for 60 minutes, minimal residual bamboo was achieved with about 90% polyol yield, while other polyol properties like hydroxyl number and viscosity remained acceptable. The polyol displayed a dark-brown to almost black color, attributed to the formation of carbonyl groups (C=O) and carbon-carbon double bonds (C=C) during liquefaction. Different ratios of hydrogen peroxide (20%, 40%, 60%, and 80%) and reaction times (12 h and 24 h) were used to lighten the color of liquefied bamboo to lighter brown-yellow hue. This study attributed the lighter color polyols to hydrogen peroxide decomposition in the presence of carbonates, generating peroxycarbonate ions (CO42-). The extent of discolouration of liquefied polyols was significantly influenced by the amount of peroxide added from lowest to highest. Bio-polyurethane films were prepared by mixing the liquefied bamboo (unbleached and bleached) with polymeric diphenylmethane diisocyanate at four ratios (w/w 1.6, 1.8, 2.0, and 2.2) and dried at ambient temperature for 24 hours before being heated in an oven at 80 °C for 8 h, and were characterised by FTIR, TGA, DMA, tensile, water absorption, and indoor soil degradation test. The study’s finding suggest that the bleaching sequence used did not notably affect the film’s properties. The bio-polyurethane was brushed onto rubberwood lumber and cured in an 80 °C oven for 30 minutes. The coated wood surface was examined for adhesion, scratch, abrasion, impact, and resistance to common household resistance. The coated biopolyurethane exhibited favourable finishing characteristics and demonstrated resistance to common household chemicals. Bleaching liquefied bamboo polyols did result in significant changes to the surface properties, with unbleached polyols showing higher scratch and impact resistance compared to bleached bio-polyurethane. However, adhesion and abrasion properties were similar in both cases. This research discovered a method to produce transparent bio-polyurethane from bamboo biomass for wood finishing, offering an alternative use for bamboo residue and expanding the range of biopolyurethane coating materials.